Dissecting the genetic architecture of key agronomic traits in lettuce using a MAGIC population - Hongyun Chen; Jiongjiong Chen; Ruifang Zhai; Dean Lavelle; Yue Jia; Qiwei Tang; Ting Zhu; Menglu Wang; Zedong Geng; Jianzhong Zhu; Hui Feng; Junru An; et al. (Genome Biology)
Abstract Background Lettuce is a globally important leafy vegetable that exhibits diverse horticultural types and strong population structure, which complicates genetic analyses. To address this challenge, we develop the first multi-parent, advanced generation inter-cross (MAGIC) population for lettuce using 16 diverse founder lines. Results Whole-genome sequencing of the 16 founder lines and 381 inbred progeny reveal minimal population structure, enabling informative genome-wide association studies (GWAS). GWAS of the lettuce MAGIC population identifies numerous loci associated with key agricultural traits, including 51 for flowering time, 11 for leaf color, and 5 for leaf shape. Notably, loss-of-function mutations in the LsphyB and LsphyC genes, encoding phytochromes B and C, dramatically delay flowering in lettuce, which is in striking contrast to many other plant species. This unexpected finding highlights the unique genetic architecture controlling flowering time in lettuce. The wild-type LsTCP4 gene plays critical roles in leaf flatness and its expression level is negatively correlated with leaf curvature. Additionally, a novel zinc finger protein (ZFP) gene is required for the development of lobed leaves; a point mutation leads to its loss of function and consequently converted lobed leaves to non-lobed leaves, as exhibited by most lettuce cultivars. Conclusions The MAGIC population’s lack of structure and high mapping resolution enables the efficient dissection of complex traits. The identified loci and candidate genes provide significant genetic resources for improving agronomic performance and leaf quality in lettuce.